Aims and Results of Partial Privatization - Lazutka, Romas (Ekonomika, 2008)
The public pension system in Lithuania was founded in 1990 when a social insurance fund, autonomous from the state budget, was established. The economic decline, high inflation, rising unemployment, the high number of those not participating in social insurance during the 1992-2000 period imposed hardships on the pension system. From the beginning of 1994, the non-governmental organisation libertarian Lithuanian Free Market Institute and Lithuanian business organisation of the Industrialists Confederation started advocating for the private pension provision. Most commonly referred arguments came from the World Bank edition Averting the Old Age Crisis. The main argument was: due to the ageing of population Lithuania, like other industrial countries, is facing challenges in providing income security for the elderly.The public pension fund financing difficulties and low pension benefits turned the Government away from social insurance towards private pension funds, beginning with the partial privatisation of the social insurance. All political parties have backed the privatisation. although with varying levels of enthusiasm (Liberals showed the highest and Social Democrats the least enthusiasm). The actual implementation of the reform was undertaken in 2004 by Social Democrats as the major partner in the coalition with Social Liberals. They chose a moderate pace and began with a small contribution and supported a voluntary switchover from social insurance to private pension funds. So, Lithuania, like some Eastern European and Latin American countries, implemented the so-called structural pension reform.The main official objective of the pension reform was to change the pension system in such a way that persons of pension age could get higher income than previously, meanwhile to ensure that the redistribution would not be increased but reduced, and to ensure the long-term financial sustainability of the system which will cover all the inhabitants. Additionally, it was expected that introduction of the private pension scheme due the pension reform will increase savings and investment and thus will promote the growth of the national economy.The key element of the reform was the transfer of 5.5 percentage points of social insurance contributions into private pension funds. However, unlike some other Eastern and Central European countries, Lithuania made its private pension system optional for employees. Persons of any age, insured by the social insurance, got the opportunity to accumulate part of their social insurance contributions in a personal account of private pension funds.During the first four years of the pension reform, by the end of2007, there were signed more than 800 thousand pension accumulation contracts between employees and managers of private pension funds. Thus, already at the beginning of the reform, almost 70 per cent of the insured for the full social insurance pension decided to participate in private pension funds. There are six assets managers and three private insurance companies in the Lithuanian pension market. They have accumulated the pension capital close to 1.7 billion Litas. Annual money transfer from the Social Insurance Fund to private pension funds (transitional costs of the reform) has reached I per cent of the GDP in 2008.Financing pension reform transitional costs comes into conflict with the financing of current pensions. High transitional costs have a negative impact on the social insurance pension budget, and it will last for several decades. If these resources were left for the financing of the social insurance pensions, they would have been higher by 20 per cent. These are implicit costs of the pension reform, which that are paid by the present generation of pensioners.Alternatively, without a reform social insurance contributions could have been decreased from the current 34 per cent to 28.5 per cent. In this sense, the costs of the reform will fall on all working population and employers, meanwhile only part of employees participate in the reform.The pension reform history’ is too short for evaluation of its benefit for the private pension fund participants. Nevertheless, capital returns from pensions’ assets hardly overcome inflation during the first four years of the reform. Because the high private pension fund administration costs erode participants’ savings, the government needs to place a tighter control on administrative costs.The earning-related part of the social insurance pension will be reduced for participants of the private pension funds proportionally to the reduced part of the contribution for the social insurance (about 30 per cent) due to the fact that part of the contribution has been transferred to the private pension fund. Because of a rapid increase of public pensions, the loss of the reform participants will be substantial. In this respect, the State’s commitments and the scope of social security to the future pensioners will be reduced by the part of the privatised pension. It is not in line with the ILO Convention N 102 which says that the State must take responsibility for the social security benefit.Prior to the reform, one of the arguments was the necessity to increase investment into the national economy. However, 90 per cent of pensions’ assets are invested abroad, and there are very few investments into shares of domestic companies. Moreover, heavy investments in public versus private assets, high administrative costs, the oligopolistic pension industry, and low competition because of consumers’ myopia have a negative impact on the future pensions’ benefits.All the parties involved in the reform designing argued for the necessity of reform implementation by referring to the current problems which cannot be resolved by the reform. Moreover, they set objectives that may hardly be obtained by the reform in its implementation. The content of the reform is very narrow if compared with what was planned at the beginning of the reform discussion and what the initial reform documents mentioned. On the contrary, the reform has a list of negative consequences on the current and future pensioners’ welfare.